2023
DOI: 10.1093/cid/ciad401
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Adjunctive High-Dose Infliximab Therapy to Improve Disability-Free Survival Among Patients With Severe Central Nervous System Tuberculosis: A Matched Retrospective Cohort Study

Abstract: Background Few treatment options exist for patients with severe central nervous system tuberculosis (CNS TB) worsening due to inflammatory lesions, despite optimal antitubercular therapy (ATT) and steroids. Data regarding the efficacy and safety of infliximab in these patients is sparse. Methods We performed a matched retrospective cohort study based on Medical Research Council (MRC) grading system and modified Rankin Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The median duration from start of ATT and corticosteroid treatment was six months. The cohort only included one PLWH ( 126 ). A randomised trial is needed to investigate whether these improved outcomes with infliximab are seen more generally when administered alongside ATT from diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The median duration from start of ATT and corticosteroid treatment was six months. The cohort only included one PLWH ( 126 ). A randomised trial is needed to investigate whether these improved outcomes with infliximab are seen more generally when administered alongside ATT from diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…There were 5 studies representing 806 participants that evaluated the impacts of interventions in preventing post-TB neurological sequelae such as neuromotor disability, hemiparesis, quadriparesis, and neurological deficits ( Table 5 ). 33 , 34 , 35 , 36 , 37 The overall incidence rate of neurological sequelae was 282 per 1000 TB survivors (239 per 1000 TB survivors in the intervention group and 330 per 1000 TB survivors in the control group). We identified two main components of interventions delivered in the study: adjunctive therapy and rehabilitation programs.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have investigated the effects of rehabilitation programs and adjunctive therapy on preventing post-TB neurological impairment and findings are inconsistent. 33 , 34 , 35 , 36 , 37 The pooled meta-analysis of adjunctive therapy revealed no statistically significant difference in neurological impairment incidence between the intervention and control groups, whereas a separate study on rehabilitation programs showed a significant reduction in neurological impairment within the intervention group compared to controls. While these findings suggest the potential benefit of rehabilitation programs in preventing neurological sequelae following TB treatment, further studies are needed to establish conclusive evidence.…”
Section: Discussionmentioning
confidence: 96%
“…Forty of 90 patients had a paradoxical reaction, 19 of whom were treated with infliximab. Overall, infliximab treatment was the only parameter associated with disability-free survival at 6 months [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…It ranges from symptomatic treatment to predominantly anti-inflammatory approaches, often including corticosteroid therapy [ 13 ]. Paradoxically, a handful of studies report the use of anti-TNFα agents in this context [ 14 , 15 ].…”
mentioning
confidence: 99%